THE VALUE CHAIN OF FISH FOR FLOATING CAGES AND POND TECHNIQUES IN BAGHDAD PROVINCE - & et al., AL- Flujy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The fish sector is considered an important  component of the economies of  many countries in the  world  including Arab countries . This work is considered as the  first  attempt to study value  chain for fish in Iraq. The objective of  this  study is  to identify the main problems and  constraints  facing    different  channels  or  links  the  value  chain of  fish, and  to analyse  revenue, production costs, and to  calculate some  quantitative  indicators  like  value  added . The results  showed  that  average  value  added  of  the  different  links are amount: 22.13dinars/kg, 1007.7 dinar/kg, 242.9 dinar/kg and 1023.5 dinars/kg from each links hatcheries, producers, wholesalers and  retailers , the  results also showed  that  the share  of  different  links from value chain  for average value  additionrs  as  follows : 0.96% for  hatcheries link , 43.8% for producer link , 10.6% for  wholesalers  link and 44.6%  for  retailers  link. While  cages producers  added  68.5%  from average  value  added  it is amount  2796. 9 dinar/ kg on level techniques  of  floating cages . The study also identifis the main challenges and  problems  facing  each link in chain  value  and  forward  the  suitable  solution  and  recommendation  for  government  Authorities and private sector  in  order  to  increase the  efficiency of  fish  in  Iraq .